Nothing's Imperative: Late Beckett. Issue 2 (2nd April 2016) - Stables, Wayne
Summary: This article dwells on the imperative to say "nothing", concentrating its attention, for the most part, on Worstward Ho . It aims to illuminate the imperative's temporality as well as to account for its origin. It is suggested that Beckett's late writing is best approached not by way of phenomenology but from what Walter Benjamin calls the "fundamental problem of the theory of language" (2007: 316; trans. modified): the question of the medial matter of language as such.